The role of terminology and its comparison with lexicology in linguistics (Eurasian Research Bulletin, 2023)
This article illustrates the importance of terminology and also the comparison of terminology and lexicology. In this article general information about terminology is given. Terminology helps individuals realize the interaction between the units of specialized texts and the whole context which is often a subconscious mechanism of knowledge acquisition. It also develops interests in the formation of new words and terms